2001
DOI: 10.1080/10903120190940137
|View full text |Cite
|
Sign up to set email alerts
|

S Ubcutaneous E Pinephrine in the P Rehospital S Etting

Abstract: The authors did not find significant evidence to contraindicate the use of subcutaneous epinephrine in older patients who are not known to have coronary artery disease, who present with either asthma or allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Although it is unclear how significant the allergic reaction (tongue swelling) was in our patient before epinephrine administration, the patient reported only minimal resolution of her symptoms upon arrival to the ED, and our initial physical examination revealed only mild lingual edema and lack of any airway compromise. A recent systematic literature review failed to reveal evidence to contraindicate the use of intramuscular epinephrine in older patients who are not known to have coronary artery disease (24). However, in the absence of impending airway compromise, cardiovascular collapse, or true anaphylaxis, it may be prudent to carefully consider the potential risks of intramuscular epinephrine when deciding whether its administration is warranted based upon the presentation and severity of the allergic reaction, particularly in elderly patients.…”
Section: Discussionmentioning
confidence: 91%
“…Although it is unclear how significant the allergic reaction (tongue swelling) was in our patient before epinephrine administration, the patient reported only minimal resolution of her symptoms upon arrival to the ED, and our initial physical examination revealed only mild lingual edema and lack of any airway compromise. A recent systematic literature review failed to reveal evidence to contraindicate the use of intramuscular epinephrine in older patients who are not known to have coronary artery disease (24). However, in the absence of impending airway compromise, cardiovascular collapse, or true anaphylaxis, it may be prudent to carefully consider the potential risks of intramuscular epinephrine when deciding whether its administration is warranted based upon the presentation and severity of the allergic reaction, particularly in elderly patients.…”
Section: Discussionmentioning
confidence: 91%
“…This may be because physicians were reluctant to give epinephrine to older patients who are more likely to have cardiovascular comorbidities. However, there is no data to suggest that a history of known coronary artery disease is a contraindication to epinephrine 17. Alternatively, it is possible that younger patients had more severe or persistent symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Horowitz et al reported a fatal intracranial bleed associated with field administration of 0.5 mg of epinephrine in a misdiagnosed case of anaphylaxis despite presence of a contraindication (severe hypertension) (22). There are also risks of other non-fatal but potentially serious complications (21,23). Although the literature does not suggest that field use of epinephrine is unsafe, the literature to date is based only on paramedic-level administration of epinephrine.…”
Section: Introductionmentioning
confidence: 93%